Design and characterization of variable stiffness structural joints. (February 2020) - Wang, Qinyu; Senatore, Gennaro; Jansen, Kaspar; Habraken, Arjan; Teuffel, Patrick
Abstract: This paper presents design and characterization of a new type of structural joint which can vary its stiffness through actuation. Stiffness variation is employed to control the dynamic response of frame structures equipped with such joints. The joint is made of a shape memory polymer (SMP) core which is reinforced by an SMP-aramid composite skin. A controlled stiffness reduction of the joint core material, induced by resistive heating, results in a shift of the structure natural frequencies. This work comprises two main parts: 1) characterization of material thermomechanical properties and viscoelastic behavior; 2) numerical simulations of the dynamic response of a one-story planar frame equipped with two such variable stiffness joints. The experimental material model obtained through Dynamic Mechanical Analysis has been used to carry out modal and non-linear transient analysis. However, control time delays due to heating and cooling as well as fatigue are not considered in the numerical simulations. Results have shown that through joint stiffness control, the fundamental frequency shifts up to 8.72% causing a drastic reduction of the dynamic response under resonance loading. The SMP-aramid skin is effective to restrain the joint deformation in the activated state while maintaining viscoelastic damping properties. Graphical abstract: Unlabelled Image Highlights: Design and characterization of variable stiffness structural joints to control the dynamic response of frame structures. The joint consists of a shape memory polymer (SMP) core and an SMP-aramid composite skin. Stiffness reduction of the joint core through resistive heating causes a shift of the structure natural frequencies. The natural frequency shift significantly reduces up to 84% of the maximum displacement under resonance loading. The composite skin effectively restrains the joint core deformation while having a marginal effect on viscoelastic damping.